Peripheral blood natural killer cells and mild thyroid abnormalities in women with reproductive failure. (March 2016) - Triggianese, P; Perricone, C; Conigliaro, P; Chimenti, MS; Perricone, R; De Carolis, C
Abnormalities in peripheral blood natural killer (NK) cells have been reported in women with primary infertility and recurrent spontaneous abortion (RSA) and several studies have been presented to define cutoff values for abnormal peripheral blood NK cell levels in this context. Elevated levels of NK cells were observed in infertile/RSA women in the presence of thyroid autoimmunity (TAI), while no studies have been carried out, to date, on NK cells in infertile/RSA women with non-autoimmune thyroid diseases. The contribution of this study is two-fold: (1) the evaluation of peripheral blood NK cell levels in a cohort of infertile/RSA women, in order to confirm related data from the literature; and (2) the assessment of NK cell levels in the presence of both TAI and subclinical hypothyroidism (SCH) in order to explore the possibility that the association between NK cells and thyroid function is not only restricted to TAI but also to SCH. In a retrospective study, 259 age-matched women (primary infertility [n = 49], primary RSA [n = 145], and secondary RSA [n = 65]) were evaluated for CD56+CD16+NK cells by flow cytometry. Women were stratified according to thyroid status: TAI, SCH, and without thyroid diseases (ET). Fertile women (n = 45) were used as controls. Infertile/RSA women showed higher mean NK cell levels than controls. The cutoff value determining the abnormal NK cell levels resulted ⩾15% in all the groups of women. Among the infertile/RSA women, SCH resulted the most frequently associated thyroid disorder while no difference resulted in the prevalence of TAI and ET women between patients and controls. A higher prevalence of women with NK cell levels ⩾15% was observed in infertile/RSA women with SCH when compared to TAI/ET women. According to our data, NK cell assessment could be used as a diagnostic tool in women with reproductive failure and we suggest that the possible association between NK cell levels and thyroid function can be described not only in the presence of TAI but also in the presence of non-autoimmune thyroid disorders.